Deregulation of DNA-dependent protein kinase catalytic subunit contributes to human hepatocarcinogenesis development and has a putative prognostic value - Evert, M (Nature Publishing Group, 2013)
BACKGROUND: The DNA-repair gene DNA-dependent kinase catalytic subunit (DNA-PKcs) favours or inhibits carcinogenesis, depending on the cancer type. Its role in human hepatocellular carcinoma (HCC) is unknown. METHODS: DNA-dependent protein kinase catalytic subuni, H2A histone family member X (H2AFX) and heat shock transcription factor-1 (HSF1) levels were assessed by immunohistochemistry and/or immunoblotting and qRT–PCR in a collection of human HCC. Rates of proliferation, apoptosis, microvessel density and genomic instability were also determined. Heat shock factor-1 cDNA or DNA-PKcs-specific siRNA were used to explore the role of both genes in HCC. Activator protein 1 (AP-1) binding to DNA-PKcs promoter was evaluated by chromatin immunoprecipitation. Kaplan–Meier curves and multivariate Cox model were used to study the impact on clinical outcome. RESULTS: Total and phosphorylated DNA-PKcs and H2AFX were upregulated in HCC. Activated DNA-PKcs positively correlated with HCC proliferation, genomic instability and microvessel density, and negatively with apoptosis and patient's survival. Proliferation decline and massive apoptosis followed DNA-PKcs silencing in HCC cell lines. Total and phosphorylated HSF1 protein, mRNA and activity were upregulated in HCC. Mechanistically, we demonstrated that HSF1 induces DNA-PKcs upregulation through the activation of the MAPK/JNK/AP-1 axis. CONCLUSION: DNA-dependent protein kinase catalytic subunit transduces HSF1 effects in HCC cells, and might represent a novel target and prognostic factor in human HCC.